Pemanfaatan E-Commerce Untuk Mendorong Generasi Muda Menjadi Wirausaha Baru Pada Siswa SMA Negri 105 di Kelapa Dua Wetan, Jakarta Timur - Sari Puspitarini (Universitas Mercu Buana, 2023)
Electronic commerce or E-commerce or in Indonesian Electronic Commerce is all buying and selling activities carried out through electronic media. Therefore E-commerce activities include distributing, selling, purchasing, marketing products (goods and services), by utilizing telecommunications networks such as the internet, television, or other computer networks. Although the means include television and telephone, E-commerce is now more common via the internet. State Senior High School 105 is one of the secondary schools that educates its students in carrying out school activities, so that they are programmed and directed according to its mission